Desa E-Commerce Taobao sebagai Kekuatan Ekonomi Tiongkok dalam Mentransformasikan Perekonomian dan Kesenjangan Sosial di Pedesaan - Hendrini Renolafitri (Insignia: Journal of International Relations, 2020)
Abstract This study examines the Taobao e-commerce village as China’s economic strategis to reduce poverty amd social inequality. The Taobao generated RMB 3 trillion (more than USD 430 billion) in just one year in 2013. The success of Taobao not only profound effect for the villages registered in e-commerce area, but also for the villages surrounding the areas. The development of the Taobao village has also been able to transform the rural economy, and its livelihood, especially providing economic opportunities for people living in rural and remote areas in China to contribute to local, regional, and international markets through unlimited e-commerce systems. The purpose of this study is to review the development of rural Chinese e-commerce with examples of Taobao villages, and evaluate the extent of Taobao villages transformative impact on the Chinese rural economy. Another purpose of this study is to show the opportunity of developing the rural e-commerce system to developing countries, expecially Indonesia which composed with diversity of distinctive industrial of rural communities that can be a distinct competitive advantage in international market. This study uses qualitative methods, with library data analysis techniques, by collecting data from books and website. The result of this study indicate a comparison of the two generations of e-commerce development in China, proove that the success of this strategy is the agregationand full support from the government’s, by producing many policies in order to develop the village. Kata Kunci: China E-Commerce, Taobao Villages, China Poverty Reduction, China’s Urban – Rural Disparity. Abstract This study examines the Taobao e-commerce village as China’s economic strategis to reduce poverty amd social inequality. The Taobao generated RMB 3 trillion (more than USD 430 billion) in just one year in 2013. The success of Taobao not only profound effect for the villages registered in e-commerce area, but also for the villages surrounding the areas. The development of the Taobao village has also been able to transform the rural economy, and its livelihood, especially providing economic opportunities for people living in rural and remote areas in China to contribute to local, regional, and international markets through unlimited e-commerce systems. The purpose of this study is to review the development of rural Chinese e-commerce with examples of Taobao villages, and evaluate the extent of Taobao villages transformative impact on the Chinese rural economy. Another purpose of this study is to show the opportunity of developing the rural e-commerce system to developing countries, expecially Indonesia which composed with diversity of distinctive industrial of rural communities that can be a distinct competitive advantage in international market. This study uses qualitative methods, with library data analysis techniques, by collecting data from books and website. The result of this study indicate a comparison of the two generations of e-commerce development in China, proove that the success of this strategy is the agregationand full support from the government’s, by producing many policies in order to develop the village. Keywords: China E-Commerce, Taobao Villages, China Poverty Reduction, China’s Urban – Rural Disparity.